KOMPETISI PASAR PRODUK DAN BIAYA AUDIT: SPESIALISASI INDUSTRI AUDITOR SEBAGAI VARIABEL MODERASI - Salma Anastasya Maharani; Rita Wijayanti (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to analyze the effect of product market competition on audit fees with auditor industry specialization as a moderating variable. The Existing theory places two contradictory predictions about the relationship between product market competition and audit fees. On the one hand, product market competition can reduce agency problems, but on the other hand product market competition can increase auditors' assessment of business risk. By using data from the financial statements of basic and chemical industry sub-sector companies listed on the Indonesia Stock Exchange from 2017 to 2020, 180 companies were obtained using the probability method as a research sample. This study uses multiple linear regression analysis techniques to analyze the data. The results show that product market competition has a significant positive effect on audit fees and auditor industry specialization has a significant negative effect or strengthens the relationship between product market competition and audit fees. In other words, industry specialization auditors charge lower audit fees even in a competitive market.